Delegitimizing, corruptive crises - Ángel R. Oquendo (Revista Direito GV)
Abstract Without doubt, pervasive corruption may undermine a government's legitimacy. Citizens may lose faith in political and legal institutions and become cynical or rebel. Ultimately, the very survival of the polity may be at stake. This paper deals with these issues, but at a rather specific conceptual level. In particular, it explores the notion of a legitimation crisis and its implications for the issue of corruption in Latin America. This exercise will make it possible to appreciate how corrupt practices debilitate the state's claim to justification. Indeed, the notion of a legitimation crisis helps to illuminate the problem of governmental dishonesty in Latin America. If properly reinterpreted, it enables one to grasp corruption as an endemic threat to the normative identity of the national communities. The concept may describe a situation in which these collectivities must, at the outset, transition from an instrumental to a reflexive construction of legitimacy norms, such as autonomy, legality, and equality, in order effectively to regenerate a corrupt bureaucracy and, thereafter, struggle to recognize themselves after the changeover. Accordingly, one should not respond to the challenge exclusively in a technical manner, such as with the enactment of tougher laws or with the implementation of more drastic enforcement mechanisms. Nor should one take a merely motivational approach, in the sense of U.S. psychologist David McClelland, rather than that of Habermas. In other words, one should not solely seek to change the attitude or the prevailing professional culture in civil service. Instead, Latin American societies must embark upon an unlikely radical crusade to transform the way in which they understand themselves, particularly the premises of their social integration. Against all odds, they must genuinely commit to and identify with democracy, the rule of law, and solidarity.